Using FunSeq2 for Coding and Non‐Coding Variant Annotation and Prioritization. Issue 1 (2nd May 2017) - Dhingra, Priyanka; Fu, Yao; Gerstein, Mark; Khurana, Ekta
Abstract: The identification of non‐coding drivers remains a challenge and bottleneck for the use of whole‐genome sequencing in the clinic. FunSeq2 is a computational tool for annotation and prioritization of somatic mutations in coding and non‐coding regions. It integrates a data context made from large‐scale genomic datasets and uses a high‐throughput variant prioritization pipeline. This unit provides guidelines for installing and running FunSeq2 to (a) annotate and prioritize variants, (b) incorporate user‐defined annotations, and (c) detect differential gene expression. © 2017 by John Wiley & Sons, Inc.